Audiovestibular performance in patients with low bone mineral density: a case-control study - Mohamed Elwan; Mohamed M Elmoursy; Ahmed M Ibrahim Metwaly; Mohamed M Ryan (Wolters Kluwer Medknow Publications, 2022)
Background and aim Audiovestibular dysfunctions have been previously linked to osteoporosis (OP) with controversies about the mutual relationship. In this study, we aimed to assess the audiovestibular functions in patients with OP and osteopenia and to study their association with vitamin D deficiency. Patients and methods Of 60 patients enrolled in this study, 30 had low bone mineral density (BMD) (group I) and 30 had normal BMD (group II). After clinical examination and evaluation of serum vitamin D and calcium levels, the participants then were referred for audiovestibular assessments, which included basic audiological evaluation by pure tone audiometry and speech audiometry, tympanometry, acoustic reflex, video-nystagmoscopy tests, and vestibular-evoked myogenic potential (VEMP) to assess saccular function. Both participants and audiologist were blinded regarding the BMD results. Results There was a significant difference between patients and controls regarding the level of calcium (P=0.002) and vitamin D (P=0.001). There was a significant difference in the normal hearing threshold between both groups (P=0.005). There was no significant difference in VEMP testing (VEMP P1; P=0.489, amplitude; P=0.898). Benign paroxysmal positional vertigo was the most common finding in group I, among the females, where they had vitamin D deficiency (16.67±4.16) and OP (mean T score=−2.73±0.06). Conclusions Patients with low BMD showed a greater degree of audiovestibular dysfunction, which should be considered among the associating risk factors and comorbidities. Assessment of the audiovestibular functions should be recommended for patients with low BMD in the management guidelines.